Pengaruh Penerapan Pendekatan Contextual Teaching and Learning (CTL) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Aty Nurdiana; Destia Rini; Eva Febriana (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2022)
The problem in this study is the low ability of students' mathematical problemsolving in learning mathematics. The purpose of this study was to determine the effectof applying the contextual teaching and learning approach to the mathematicalproblem solving abilities of Grade VIII students in odd semesters of SMP Negeri 34Bandar Lampung in the 2022/2023 academic year. This study used an experimentalmethod with the population in this study, namely all students of class VIII Odd SemesterSMP Negeri 34 Bandar Lampung, while two classes were taken as samples, namelyclass VIII B which used a contextual teaching and learning approach, and class VIII Awhich used a conventional approach. Samples were taken using the Cluster RandomSampling technique. To find out students' mathematical problem solving abilities, a testwas carried out in the form of an essay of five questions which had previously beentested for validity and reliability. Hypothesis testing in this study uses the t-hit formula.From the results of testing the hypothesis using the t-hit statistical formula, the valueof t hit = 2.60 is obtained. From the t distribution table at a significant level of 5% it isknown that t daf = 1.67, then t hit > t daf , which means that the average mathematicalproblem solving ability of students using the contextual teaching and learningapproach is higher than the average mathematical problem solving ability of studentsusing the conventional.